(untitled) (Acta Education, 2024)
This article explores the relationship between education and gender equality by analyzing various factors that influence the educational achievements of men and women. It proposes prospective measures to overcome existing gender barriers in the educational sphere and conducts a literature review on the topic, including studies conducted in various countries around the world. Based on the data analysis, the article identifies the main problems associated with gender inequality in education, such as gender stereotypes, and suggests ways to address these problems. The article is relevant to researchers interested in issues related to gender, sexuality, education, and social justice, and can be used as a basis for developing strategies and programs to improve the status of women in the education field.